Estrogen receptor and progesterone receptor genes are expressed differentially in mouse embryos during preimplantation development. - Hou, Q (1993)
Estrogen and progesterone play an important role in the development and implantation of preimplantation embryos. However, it is controversial whether these hormones act directly on the embryos. The effects of these hormones depend on the existence of their specific receptors. To determine whether estrogen receptor (ER) and progesterone receptor genes are expressed in mouse preimplantation embryos, we examined RNA from embryos at different stages of preimplantation development by reverse transcription-polymerase chain reaction techniques. ER mRNA was found in oocytes and fertilized eggs. The message level began to decline at the two-cell stage and reached its lowest level at the five- to eight-cell stage. ER mRNA was not detectable at the morula stage but reappeared at the blastocyst stage. Progesterone receptor mRNA was not detectable until the blastocyst stage. The embryonic expression of ER and progesterone receptor genes in the blastocyst suggests a possible functional requirement for ER and progesterone receptor at this stage of development. These results provide a basis for determining the direct role of estrogen and progesterone in preimplantation embryos.